PENGARUH PENGGUNAAN METODE PERMAINAN TERHADAP PENINGKATAN PENGUASAAN KOSA KATA BAHASA INGGRIS - Maya sari; Oyib Sulaeman; Fitri Annisa (Latifah Pres, 2019)
The effect of lack using game method in English subject is students in MI Condong Jamanis have low score in English vocabulary mastery. The problems that arise whether the game method has positive influence on increasing student`s English vocabulary mastery in Madrasah Ibtidaiyyah Condong or not. The assumption of this study is the game method has positive impact on student`s on increasing student`s English vocabulary mastery in Madrasah Ibtidaiyah (MI) Condong Jamanis. This aim of the study is to determine the effect of using the game method on increasing English vocabulary mastery in the Madrasah Ibtidaiyyah Condong. This research is useful for English language teachers, students and also the development of teaching materials in English subjects related to learning methods, especially game methods and efforts to improve student`s English vocabulary mastery.The method of the study is descriptive method with quantitative approach to reveal the current situation / condition by considering the past situation through the processing of numbers obtained from research Based on the results of data processing, it is found that the use of the game method in Madrasah Ibtidaiyah Condong is sufficient (x ̅ = 41, is on the scale of interpretation 40 - 44 with moderate classification). Whereas Student`s English vocabulary mastery in MI Condong has low score (x ̅ = 40, is on the scale of interpretation 38 - 41 with less classification). And the effect of using game method on increasing student`s English vocabulary mastery in Madrasah Ibtidaiyah Condong has a significant positive influence categories, it is proven that rs = 0.46 is in the interval 0.41 - 0.71 and t_count (2.76) and table (2,048). The effect of using game method influences on the increasing of English vocabulary mastery about 21%, while the left about 79% is determined by other factors, namely the use of other learning methods, habituation, the teacher always explores the game method, the students' understanding of the vocabulary given.